Role of IGF2 in the Study of Development and Evolution of Prostate Cancer - Porras-Quesada, P.; González-Cabezuelo, JM.; Sánchez-Conde, V.; Puche-Sanz, I.; Arenas-Rodríguez, V.; García-López, C.; Flores-Martín, JF.; Molina-Hernández, JM.; Álvarez-Cubero, MJ.; Martínez-González, LJ.; Vázquez-Alonso, F. (Frontiers in Genetics, 2022)
Prostate Cancer (PC) is commonly known as one of the most frequent cancers in males. One of the main problems of this tumor is that in early stages most of the cases course as indolent form, so an active surveillance will anticipate to the appearance of aggressive stages. One of the main strategies in medicine and biomedical research is to find non-invasive biomarkers for improving monitoring and follow-up of diseases like PC, where there are scarce molecular biomarkers. Here we report the relevant role of IGF2 and miR-93-5p as non-invasive biomarkers for PC. This event could improve current medical strategies in PC.